Italica Matritensia. Atti del IV Convegno Silfi, Madrid, 27 - 29 Giugno, a cura di Mª T. Navarro Salazar. Firenze, Franco Cesati, 1998. - Pérez Belló, Gloria (Cuadernos de Filología Italiana, 1999)
Sin resumen